Kinetics and Thermodynamics of Reserpine Adsorption onto Strong Acidic Cationic Exchange Fiber - Guo, Zhanjing; Liu, Xiongmin; Huang, Hongmiao (PLOS ONE, 2015)
The kinetics and thermodynamics of the adsorption process of reserpine adsorbed onto the strong acidic cationic exchange fiber (SACEF) were studied by batch adsorption experiments. The adsorption capacity strongly depended on pH values, and the optimum reserpine adsorption onto the SACEF occurred at pH = 5 of reserpine solution. With the increase of temperature and initial concentration, the adsorption capacity increased. The equilibrium was attained within 20 mins. The adsorption process could be better described by the pseudo-second-order model and the Freundlich isotherm model. The calculated activation energy Ea was 4.35 kJ/mol. And the thermodynamic parameters were: 4.97<ΔH<7.44 kJ/mol, -15.29<ΔG<-11.87 kJ/mol and 41.97<ΔS<47.35 J/mol·K. The thermodynamic parameters demonstrated that the adsorption was an endothermic, spontaneous and feasible process of physisorption within the temperature range between 283 K and 323 K and the initial concentration range between 100 mg/L and 300 mg/L. All the results showed that the SACEF had a good adsorption performance for the adsorption of reserpine from alcoholic solution.